Symposium 1: Designing for Collaboration and Mutual Negotiation of Meaning – Boundary Objects in Networked Learning - Dirckinck-Holmfeld, Lone (Proceedings of the International Conference on Networked Learning, 2006)
This paper addresses the issue of collaborative learning and networked learning within continuing professional development. Collaborative learning is defined as the meeting of specific differences and dependencies among participants and practices within and across communities, afforded and constrained by the pedagogical design. The study explores how boundary objects serve as resources to support collaborative learning as a means of representing, learning about, and transforming knowledge. Based on a case study of course group work in a networked learning environment organized as problem oriented project pedagogy, the paper identifies the different kinds of boundary objects applied. Resting on the analysis and a typology suggested by Carlile on boundary objects and types of knowledge, the paper throws light on the students’ complex process of working together, and the different forms of knowledge brought into play. The analysis suggests methods of optimizing teaching and learning processes through conscious use of boundary objects. Theoretically, the analysis questions the typology suggested by Carlile and introduces a relational view on boundary objects and how they relate to the different forms of knowledge.